BEHAVIOR OF MINERALS OF METAMORPHIC AND METASOMATIC ROCKS IN SUPERCRITICAL AQUEOUS AND AQUEOUS-SALT SOLUTIONS - Azimov P.Ya.; Bushmin S.A.; L'vov S.N.; Dolivo-Dobrovol'skii D.V. (My University, 2007)
Examination of the interaction between minerals and aqueous fluids is important to solve a wide spectrum of petrological, mineralogical, and geochemical problems of metamorphic and postmagmatic processes. Aqueous fluid is the transporting medium for metamorphic reactions, as well as for metasomatic and hydrothermal crystallization. One of the ways to study the equilibrium between minerals and aqueous fluids is numerical modeling, which allows study of the interaction between minerals and fluids if experimental data are insufficient or experiments are difficult to perform.